Modelling the dynamics of support for a right-wing populist party: the case of UKIP. Issue 2 (2nd April 2016) - Clarke, Harold; Whiteley, Paul; Borges, Walter; Sanders, David; Stewart, Marianne
ABSTRACT: Similar to a number of other right-wing populist parties in Europe, Great Britain's United Kingdom Independence Party (UKIP) has experienced increased public support in recent years. Using aggregate data from monthly national surveys conducted between April 2004 and April 2014, time series analyses demonstrate that the dynamics of UKIP support were influenced by a combination of spatial and valence issues. A spatial issue, Euroscepticism, was fundamental, with UKIP support moving in dynamic equilibrium with changing public attitudes towards EU membership. In addition, widespread anti-immigration sentiment and dissatisfaction with the performance of the Conservative–Liberal Democrat coalition government combined with the "oxygen of publicity" to propel UKIP's surge. The political context after the 2010 general election helped as well by enabling UKIP to benefit from valence considerations. Many voters continued to doubt the competence of the major opposition party, Labour, while the Liberal Democrats were part of the government and, hence, unavailable as a protest vehicle. Since many of the forces driving UKIP support are beyond its control, the party's prospects are highly uncertain.